Examination of experienced coaches and physical education teachers' teaching methods and their perceptions regarding these methods—2023 - Demiral, Şengül; Nazıroğlu, Meltem (Frontiers in Sports and Active Living, 2024)
It is widely acknowledged that coaches and physical education teachers play an important role in supporting holistic development in children and ensuring optimal performance in the training processes carried out to acquire fundamental movements and sport-specific basic skills. However, there is a need for further information on how both groups utilize and value different teaching methods during the training. The present study aims to examine the perceptions of coaches and physical education teachers regarding the use and value of teaching methods. For this purpose, the "Coaches' Instructional Methods Utilization Scale" for coaches and the "Physical Education Teachers' Perception of Teaching Methods Scale" for physical education teachers were administered to 114 coaches and 115 physical education teachers voluntarily participating from three randomly selected provinces of Türkiye. The Cronbach Alpha values ranged between .89 and .93 for the "Coaches' Instructional Methods Utilization Scale" and between .90 and .96 for the 'Physical Education Teachers' Perception of Teaching Methods Scale'. Descriptive statistics were used in research, t-tests in binary comparisons, One-Way ANOVA in multiple comparisons, and Tukey's test in determining the source of differences. Similarities were observed in the most and least used methods by coaches and physical education teachers, as well as in their perceptions of the highest and lowest values for these methods. Additionally, coaches and physical education teachers exhibited similarities in their perceptions of value in terms of entertainment, learning, and motivation. It was observed that female physical education teachers had lower value perceptions among the levels of use of teaching methods and value perceptions according to gender. Comparing the usage levels and value perceptions of teaching methods by professional experience, significant differences were found in Exercise (B), Learner-Designed Individual Program (I), and Learner-initiated (J) methods for coaches, whereas no statistically significant difference was observed in value perceptions. Moreover, considering the physical education teachers, significant differences were found in Command (A), Self-Check (D), Guided Discovery (F), Problem-Solving: Single Solution (G) methods, and in value perceptions for the Exercise (B), Guided Discovery (F), Problem-Solving: Single Solution (G), Problem-Solving: Crating Different Paths (H), and Learner-initiated (J) values.